SUSTAINABILITY ANALYSIS OF ONION CULTIVATION IN DEMAK DISTRICT, CENTRAL JAVA PROVINCE - Inayah Rahmawati Putri Utami; Wiludjeng Roessali; Siwi Gayatri (Faculty of Animal and Agricultural Science, Diponegoro University, 2023)
Sustainable agriculture on a global scale is no exception in Demak Regency which aims to improve food productivity and has positive side effects on goods, services and the environment. Sustainable agriculture indicators vary from region to region. The purpose of this study was to determine the income and profitability and sustainability of shallot farming. The samples taken in this study were 175 shallot farmers respondent. The research method used is a survey method with three data analyses, namely income and profitability analysis and Structural Equational Modeling (SEM) analysis with the AMOS program. The results showed that the income of shallot farmers in Mijen District, Demak Regency was Rp119,319,173 per planting season with an average land area of 7,600 m2. The profitability value is 159.35%, indicating that the profitability of shallot farming is much higher than bank deposit rates, which means that this business is feasible to develop. SEM analysis shows that the exogenous variables of respondent characteristics and production input factors have a positive and significant effect on farming performance. Furthermore, exogenous environmental, social, economic and institutional variables have a positive effect on sustainability, while technological variables have no significant effect on sustainability variables. Agricultural performance has a positive relationship with sustainable agriculture. Farmers' knowledge of the use of technology in cultivation activities needs to be increased for the success of sustainable agriculture in each indicator.